Кайнотропозы — одно из главных направлений эволюционного процесса - Киршенблат, Я.Д. (Вестник зоологии, 1969)
А. N. Severtsov has indicated four chief ways of the evolutionary process by means-of which biological progress in animal kingdom is accomplished. He attached particular importance to aromorphosis by which general energy of animal activity is increased, i. e. morphophysiblogical progress is attained. A comparison of definitions of aromorphosis given by A. N. Severtsov and I. I. Schmalhausen shows that there are differences of principle between the conceptions of the both scientists. Schmalhausen united under the name of aromorphosis two different ways of the evolutionary process. One of them is aromorphosis according to the definition of A. N. Severtsov (or anagenesis of B. Rensch). For the second way a new term Cainotroposis (from the Greek xaiv6g — new and rod.ioc;— way, direction) is suggested. Cainotroposes are such ways of evolution by means of which, there appear organs or their systems accomplishing new functions in a new way. They lead to the origin of new sides in interrelations between animals and their environment. Examples of cainotroposes and aromorphoses are presented.